Factores determinantes del desarrollo de competencias financieras en los futuros profesionales de administración de empresas de universidades colombianas - Rocha Alfonso, Andrés (Editorial Uniagustiniana, 2020)
This chapter aims to identify the social, economic, and educational factors that affect the financial skills of future professionals in Business Administration programs offered by Colombian universities. For this purpose, we studied the results obtained in the specific financial management skill module of the Saber Pro tests applied to students in 2016, using the information provided by the Colombian Institute for the Promotion of Higher Education (Icfes). Data analysis was carried out through a two-level hierarchical model, which considered individual gender and age variables as the first analysis level. For the second level, the institutional variable, accredited universities, accredited pro-grams, and study modality were collected. In short, a difference in the average scores among the studied institutions was observed. In addition, the direct relationship among second-level variables and gender became relevant, whereas the relationship between age and scores turned out to be inverse.